“Em Moçambique... Epa, porra! Os Filhos dos Dirigentes Tinham uma Escola!” – Memórias de três gerações e suas narrativas escolares em África subsariana - Xénia de Carvalho (Cadernos de Estudos Africanos)
In this article it is argued that school, in a post-colonial context, is a space that (re)produces social inequalities. School is an institution that reproduces culture, a place of power in which reality is socially constructed by an elite that has been growing since colonial times until nowadays. School, in post-colonial settings, follows a Western European model and system of education. Looking at the last four decades of education in Mozambique, framed in three specific ideological and political periods, using ethnography and collection of life histories over three generations, this article aims to contribute for an understanding of learning in school as an institution, and how it contributes for the emancipation of social actors.